A Review of Removal of Pollutants from Water/Wastewater Using Different Types of Nanomaterials - M. T. Amin; A. A. Alazba; U. Manzoor (Advances in Materials Science and Engineering)
The rapidly increasing population, depleting water resources, and climate change resulting in prolonged droughts and floods have rendered drinking water a competitive resource in many parts of the world. The development of cost-effective and stable materials and methods for providing the fresh water in adequate amounts is the need of the water industry. Traditional water/wastewater treatment technologies remain ineffective for providing adequate safe water due to increasing demand of water coupled with stringent health guidelines and emerging contaminants. Nanotechnology-based multifunctional and highly efficient processes are providing affordable solutions to water/wastewater treatments that do not rely on large infrastructures or centralized systems. The aim of the present study is to review the possible applications of the nanoparticles/fibers for the removal of pollutants from water/wastewater. The paper will briefly overview the availability and practice of different nanomaterials (particles or fibers) for removal of viruses, inorganic solutes, heavy metals, metal ions, complex organic compounds, natural organic matter, nitrate, and other pollutants present in surface water, ground water, and/or industrial water. Finally, recommendations are made based on the current practices of nanotechnology applications in water industry for a stand-alone water purification unit for removing all types of contaminants from wastewater.